2019
DOI: 10.1021/acs.langmuir.9b01476
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Phospholipid Modified Membrane Degradation Catalyzed by a Secreted Phospholipase A2

Abstract: To optimize the compositions of the lipid-based nanomedicine and to advance understanding of the roles of polyunsaturated phospholipids in biological membranes, this study examined the effects of polyunsaturated phospholipids on the degradation of giant unilamellar vesicles catalyzed by a secreted phospholipase A2 (sPLA 2 ) using fluorescence microscopy. Molecular interfacial packing, interaction, and degradation of the films containing various mixing ratios of saturated and polyunsaturated phospholipids were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…All the films were exposed to sPLA 2 for 2 h before the XR and GIXD measurements on the degraded films. Our previous studies showed that after DPPC degradation, the interface was covered by monolayer liquid-phase domains of lysoPC accompanied by highly ordered inverted bilayer and trilayer domains of PA-Ca 2+ complexes with oblique packing structures. The degraded films of DPPC with different amounts of DPPE-PEG5k also contained monolayer domains mixed with inverted bilayer domains of PA-Ca 2+ complexes; however, trilayer domains were not detectable, and a remarkable amount of PA molecules maintained hexagonal packing in the monolayer domains (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…All the films were exposed to sPLA 2 for 2 h before the XR and GIXD measurements on the degraded films. Our previous studies showed that after DPPC degradation, the interface was covered by monolayer liquid-phase domains of lysoPC accompanied by highly ordered inverted bilayer and trilayer domains of PA-Ca 2+ complexes with oblique packing structures. The degraded films of DPPC with different amounts of DPPE-PEG5k also contained monolayer domains mixed with inverted bilayer domains of PA-Ca 2+ complexes; however, trilayer domains were not detectable, and a remarkable amount of PA molecules maintained hexagonal packing in the monolayer domains (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…Sustained release of encapsulated drugs from PEGylated lipid vesicles, compared to the vesicles without PEG conjugation, has been reported. , Enzyme-catalyzed degradation of the lipids results in the formation of the heterogeneous structures of loosely packed lysoPC and highly organized multilayer domains of PA–Ca 2+ complexes, which induces the holes on the vesicles and thus causes leakage of the encapsulated drug. ,, The impeding effects of PEG conjugation on lysoPC and PA microphase separation and thus the formation of the heterogeneous structures provide a possible mechanistic explanation of the sustained drug release from PEGylated lipid vesicles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The X-ray wavelength was 1.24 Å. Details of the experimental setup were described in our previous publications. Briefly, a custom-made Langmuir trough (78 mm × 177.6 mm) with a single barrier was filled with 60 mL of PBS buffer. The trough is placed inside a gastight box.…”
Section: Methodsmentioning
confidence: 99%